2019
DOI: 10.1111/vsu.13172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tibial rotation on the tibial plateau angle measurement in dogs: An ex vivo study

Abstract: Objective: To determine the effect of tibial rotation on radiographic tibial plateau angle (TPA) measurement in normal and cranial cruciate ligament (CrCL)-deficient stifles. Study design: Cadaveric study. Sample population: Five pairs of canine cadaver hind limbs with no stifle osteoarthritis. Methods: Mediolateral radiographs of each specimen were obtained at 0 , 10 , 20 , and 30 of internal and external rotation of the tibia with both intact and transected CrCL. Two Kirschner wires were placed at the crania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…1 The tibial plateau-leveling osteotomy (TPLO) procedure is a common technique to stabilize cranial cruciate ligament (CCL)-deficient stifles. 2,3 Many complications have been identified and reported following TPLO. The recording of surgical complications has been standardized by Cook et al They are reported as minor, major, and catastrophic with timeframes reported as perioperative, and short term, intermediate, or long term.…”
Section: Introductionmentioning
confidence: 99%
“…1 The tibial plateau-leveling osteotomy (TPLO) procedure is a common technique to stabilize cranial cruciate ligament (CCL)-deficient stifles. 2,3 Many complications have been identified and reported following TPLO. The recording of surgical complications has been standardized by Cook et al They are reported as minor, major, and catastrophic with timeframes reported as perioperative, and short term, intermediate, or long term.…”
Section: Introductionmentioning
confidence: 99%
“…28 In a recent study, mediolateral radiographs of hindlimbs with intact and transected cranial cruciate ligament were obtained at 0, 10, 20 and 30 degrees of internal and external rotation of the tibia to evaluate the effect of tibial rotation on the magnitude of the tibial plateau angle measurement. 44 No differences were found in the angle measurements between the intact and transected cranial cruciate ligament at 0, 10, 20 and 30 degrees of internal and external rotation ( p > 0.05). Also, no differences were found in the tibial plateau angle measurements of intact cranial cruciate ligament between 0 degree and all degrees of internal rotation (10, 20 and 30 degrees), but the difference in angle of intact cranial cruciate ligament between 0 degree and all degrees of external rotation, 10 degrees (−1.16 degrees, p = 0.016), 20 degrees (−1.36 degrees, p = 0.001) and 30 degrees (−1.6 degrees, p < 0.001) was noted.…”
Section: Assessment Of Tibial Plateau Angle By Different Diagnostic I...mentioning
confidence: 77%
“…No difference at any rotational view of transected cranial cruciate ligament compared with 0 degrees ( p > 0.05) was found. 44…”
Section: Assessment Of Tibial Plateau Angle By Different Diagnostic I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Mediolateral radiographs of the stifle joint from each dog were used to perform the measurements. Correct positioning was determined as superposition of femoral condyles, superposition of tibial intercondylar eminences and clear delineation of the tibial plateau 18,26,29–31 . A blind investigation of the data was conducted.…”
Section: Methodsmentioning
confidence: 99%